2021
DOI: 10.1111/echo.15045
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of the presystolic wave in echocardiography and its association with the extent of coronary artery disease in patients with chronic stable angina

Abstract: Introduction Since mortality and morbidity of coronary artery disease are high, there is a need for non‐invasive diagnostic methods for early diagnosis and prediction of ischemic heart disease (IHD) outcome. This study aimed to assess the relationship between angiographic findings, the Presystolic wave (PSW) and some of the ischemic related parameters in echocardiography of the patients with chronic stable angina. Materials and methods This cross‐sectional study was conducted on the patients with chronic angin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…Our study differs from their study by the means of the studied subgroup, which is the overall systemic hypertension. The presystolic wave was associated with a higher ejection fraction (EF) after myocardial infarction (MI) [3,17]. Higher myocardial performance index, left ventricular hypertrophy (LVH), age and mitral inflow A wave have also been associated with presystolic wave [18].…”
Section: Discussionmentioning
confidence: 99%
“…Our study differs from their study by the means of the studied subgroup, which is the overall systemic hypertension. The presystolic wave was associated with a higher ejection fraction (EF) after myocardial infarction (MI) [3,17]. Higher myocardial performance index, left ventricular hypertrophy (LVH), age and mitral inflow A wave have also been associated with presystolic wave [18].…”
Section: Discussionmentioning
confidence: 99%
“…There are also studies investigating potential relationships between coronary artery disease and the lack of presystolic waves. The absence of presystolic wave was found to be predictive for extensive coronary artery disease and higher Syntax score [18,19]. Another study conducted by Saylik et al [20] revealed that presystolic wave was a common occurrence among subjects with subclinical hypothyroidism and that presystolic waves were independently associated with subclinical LV dysfunction in subjects with subclinical hypothyroidism.…”
mentioning
confidence: 94%